LES REPRÉSENTATIONS DE LA LANGUE FRANÇAISE CHEZ DES ÉLÈVES POLONOPHONES. QUEL IMPACT SUR LE CHOIX DE LA LANGUE ÉTRANGÈRE À L’ÉCOLE ? - Kucharczyk, Radosław; Szymankiewicz, Krystyna (Neofilolog, 2020)
The aim of our article is to present a study of representations of the French language among Polish high school students. Given the small percentage of pupils learning French as Foreign Language (FFL) in Poland compared to the European average (33.17% of middle school students and 23.0% of high school students in Europe against 3.3% of middle school students and 10.8% of high school students in Poland (Eurydice 2017, GUS 2018), we wondered about the role that impressions relating to French can play in the choice or rejection of FFL by young Poles. Before presenting our research results relating to this problem, we give a brief description of the Polish sociolinguistic and educational context, then we approach the notion of representation / image of languages. Next, we move to the description of the methodological framework of the empirical study that we conducted with Polish-speaking high school students (learners and non-learners in FFL) before presenting the discussion of the results. On the one hand, we examined the impressions relating to French (defined as linguistic, aesthetic, cultural, social and political phenomenon), on the other representations relating to its usefulness.